Hierarchical Sliding Mode Control for Under-actuated Cranes Design, Analysis and Simulation - Qian, Dianwei; Yi, Jianqiang; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2015)
This book reports on the latest developments in sliding mode overhead crane control, presenting novel research ideas and findings on sliding mode control (SMC), hierarchical SMC and compensator design-based hierarchical sliding mode. The results, which were previously scattered across various journals and conference proceedings, are now presented in a systematic and unified form. The book will be of interest to researchers, engineers and graduate students in control engineering and mechanical engineering who want to learn the methods and applications of SMC.
Introduction -- Mathematic model of overhead crane systems -- Sliding Mode and Sliding Mode Control -- Control of overhead cranes by traditional sliding mode methods -- Control of overhead cranes by hierarchical sliding mode methods -- Compensator design based on hierarchical sliding mode for unmodelling dynamics -- Conclusions.
Keywords: Engineering; Computer simulation; System theory; Robotics; Automation; Industrial engineering; Production engineering; Engineering; Robotics and Automation; Simulation and Modeling; Systems Theory, Control; Industrial and Production Engineering; Electronic books